LABOUR LAW TREATMENT OF HEALTH, WORK ABILITY AND PERSONAL INTEGRITY OF THE EMPLOYEES - Jovanović, Predrag (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Health and working ability are assumptions of entering into and the existence of labour relations. The purpose of entering into and the existence of labour relations is in the organised and meaningful work, in the interest of the employer and the employee. The main obligation of the employee is to do their work personally in accordance with their health and work abilities. With regards to the said abilities, the employee is accepted to the work, and protection and maintaining of these abilities is the assumption of the survival and long lasting of the employment. This makes legitimate the need that the health and work ability be protected by law in a suitable way. To that effect, we can talk about protection of health of the employees and safety at work. Since health does not only mean the absence of illness, but also the overall social security of the employees at work and in connection with work, this and issue of insurance of different risks that follow work of the employee fall into measures of health protection. Finally, not only manpower, as an organic unity of health and work abilities, takes part in labour relations, but also the entire personality of the employee with the overall personal (moral and ethical) integrity, which also on its part requires appropriate labour law treatment and protection (ban on discrimination, harassment, abuse, protection of personal data, etc.)